Al ‘Alāqāt Ad Dalāliyyah Fī Al Lugah Al ‘Arabiyyah - Abdul Hafidz Zaid (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
AbstractThe transformational doctrine founded by Chomsky has given us the ability to form countless sentences, and thus the linguistic researcher's mission is to subject all these sentences to those limited linguistic rulesand the completion of this work can not be achieved only by converting the form of a formula or some sentences to form or another formula (from the passive to the active voice, for example), so that all those sentences are subject to certain rules. The relationship between words and their meanings contains four possibilities: either these words refer to meanings in their selves, God's status to them, or to the placement of people, or to some by God and the rest by the status of men. Studies and research at the semantic level depend on the nature of the semantic relationships of words, and that the identification of the nature of the semantic relations of the words within the same language, as well as linguistic and non-linguistic means to determine the meaning is one of the foundations of the study of semantic areas and identify the distinguishing features between the words contained in each of these areas. There are many types of semantic relations between the vocabulary, including: the relationship of tandem and the relationship of verbal participation and the relationship of antagonism (or opposites in the language of the ancients).Keywords: Transformation, Meaning, Form, Nature of relationship, Words.                العلاقات الدلالية في اللغة العربية عبد الحافظ زيدجامعة دار السلام كونتورabuafadh@unida.gontor.ac.id الملخصإن المذهب التحويلي الذي أسّسه تشومسكي قد أعطانا قدرة على تكوين ما لا يُحصى من الجمل، وبذلك تكون مهمة الباحث اللغوي هي إخضاع هذه الجمل كلها لتلك القواعد اللغوية المحدودة، وإنجاز هذا العمل لا يتأتى إلا عن طريق تحويل شكل أو صيغة بعض الجمل إلى شكل أو صيغة أخرى (من المبني للمجهول إلى المبني للمعلوم مثلا)، حتى تخضع تلك الجمل كلها لقواعد معينة. تحتوي العلاقة بين الألفاظ ومعانيها على أربعة احتمالات، وهي: إما أن تدل هذه الألفاظ على المعاني بذواتها، أو وضع الله إياها، أو بوضع الناس، أو يكون البعض بوضع الله والباقي بوضع الناس. تعتمد الدراسات والبحوث في المستوى الدلالي على معرفة طبيعة العلاقات الدلالية للكلمات. و أن التعرف على طبيعة العلاقات الدلالية للكلمات داخل اللغة الواحدة، وكذلك الوسائل اللغوية وغير اللغوية لتحديد المعنى يعد من أسس دراسة المجالات الدلالية وتحديد السمات الفارقة بين الكلمات التي يضمها كل مجال من هذه المجالات، فـــهناك أنواع كثيرة من العلاقات الدلالية بين المفردات، منها: علاقة الترادف وعلاقة الاشتراك اللفظي وعلاقة التضاد (أو الأضداد في لغة القدماء).الكلمات الرئيسية: التحويلي، الدلالية، صيغة، طبيعة العلاقة، الكالمات.